Oligothiophene-Bridged Conjugated Covalent Organic Frameworks - Keller, Niklas (J Am Chem Soc, 2017)
[Image: see text] Two-dimensional covalent organic frameworks (2D-COFs) are crystalline, porous materials comprising aligned columns of π-stacked building blocks. With a view toward the application of these materials in organic electronics and optoelectronics, the construction of oligothiophene-based COFs would be highly desirable. The realization of such materials, however, has remained a challenge, in particular with respect to laterally conjugated imine-linked COFs. We have developed a new building block design employing an asymmetric modification on an otherwise symmetric backbone that allows us to construct a series of highly crystalline quaterthiophene-derived COFs with tunable electronic properties. Studying the optical response of these materials, we have observed for the first time the formation of a charge transfer state between the COF subunits across the imine bond. We believe that our new building block design provides a general strategy for the construction of well-ordered COFs from various extended building blocks, thus greatly expanding the range of applicable molecules.